Prevalence and associated factors of recurrent pregnancy loss in Nigeria according to different national and international criteria (ASRM/ESHRE vs. WHO/RCOG) - Eleje, George Uchenna; Ugwu, Emmanuel Onyebuchi; Igbodike, Emeka Philip; Malachy, Divinefavour Echezona; Nwankwo, Ekeuda Uchenna; Ugboaja, Joseph Odirichukwu; Ikechebelu, Joseph Ifeanyichukwu; Nwagha, Uchenna Ifeanyi (Frontiers in Reproductive Health, 2023)
Background In low-and middle-income countries, no conclusive research explains the prevalence and associated factors of women with a history of recurrent pregnancy loss (RPL). Some authorities have recommended further scientific research on the effect of various definitions of RPL. Objective To assess prevalence and associated factors of RPL among pregnant women in Nigeria according to different national and international criteria: the American Society for Reproductive Medicine/ European Society for Human Reproduction and Embryology (ASRM/ESHRE; two losses) and the World Health Organization/ Royal College of Obstetricians and Gynecologists (WHO/RCOG; three consecutive losses) criteria. Methods This is a cross-sectional analytical study wherein, pregnant women with prior RPL were investigated. The outcome measures were prevalence and risk factors. The associations between independent variables and outcome variable were explored using bivariate and multivariable logistic regression models. The results of these analyses were reported as adjusted odds ratios (AORs) with 95% confidence intervals (95%CI). Factors associated with RPL were identified using multivariate regression models. Result Of the 378 pregnant women interviewed, the overall prevalence of RPL in this study was found to be 15.34% (95% confidence interval = 11.65%–19.84%). The prevalence of RPL was 15.34% (58/378; 95%CI = 11.65%–19.84%) and 5.29% (20/378; 95%CI = 3.23%–8.17) according to the ASRM and the WHO criterion respectively. Regardless of diagnostic criteria, unexplained (AOR = 23.04; 95%CI: 11.46–36.32), endocrine disturbances (AOR = 9.76; 95%CI: 1.61–63.19), uterine abnormalities (AOR = 13.57; 95%CI: 3.54–50.60), and antiphospholipid syndrome (AOR = 24.59; 95%CI: 8.45–71.04) were positively and independently associated with RPL. No significant risk factors were seen when the ASRM/ ESHRE criterion vs. WHO/RCOG criterion were compared. Advanced maternal age was significantly higher in secondary than in primary type of RPL. Conclusion The prevalence of RPL was 15.34% and 5.29% according to ASRM/ESHRE and WHO/RCOG criterion respectively, with secondary type predominating. No significant differences with regard to risk factors were seen according to diagnostic criteria studied, though advanced maternal age was significantly higher in secondary RPL. Further research is needed to confirm our findings and to better characterize the magnitude of differences.